Treatment outcomes of pulp revascularization in traumatized immature teeth using calcium hydroxide and 2% chlorhexidine gel as intracanal medication - Pereira, Andrea Cardoso; Oliveira, Matheus Lima de; Cerqueira-Neto, Ana Carolina C. L.; Gomes, Brenda P. F. A.; Ferraz, Caio Cezar Randi; Almeida, José Flávio Affonso de; Marciano, Marina Angélica; De-Jesus-Soares, Adriana (Journal of Applied Oral Science, 2021)
Objective: Pulp revascularization is an effective treatment for immature necrotic teeth. Calcium hydroxide has been used in pulp revascularization as an intracanal medication due to its antimicrobial action and the non-exhibition of crown discoloration and cytotoxicity for stem cells from the apical papilla. Our study aimed to investigate the clinical success and quantitative radiographic changes of root development in immature traumatized teeth using calcium hydroxide plus 2% chlorhexidine gel as intracanal medication. Methodology: In this retrospective study, 16 patients were treated with a standardized pulp revascularization protocol. Calcium hydroxide and 2% chlorhexidine gel were manipulated in a 1:1 (v/v) ratio and inserted into root canals with Lentulo spirals (Dentsply Maillefer, Baillaigues, Switzerland). Patients were followed up for a period from 9 to 36 months for the evaluation of clinical and radiological data. Radiographic measurements of root length, root width, apical diameter, and MTA placement from the apex were quantified using software ImageJ. Wilcoxon test and t-test were used, according to nonparametric or parametric data, respectively, for changes over time in root length, root width, and apical diameter. Results: Fifteen teeth survived during the follow-up period (93.75%) and met the criteria for clinical success. Although the changes seem to be very small in many cases, significant increases in the average root length (14.28%, p<0.0001), root width (8.12%, p=0.0196), and decrease in apical diameter (48.37%, p=0.0007) were observed. MTA placement from the apex and age at the time of treatment was not significantly associated with the quantitative radiographic outcomes. Conclusions: Pulp revascularization in traumatized immature teeth treated with calcium hydroxide plus 2% chlorhexidine gel as intracanal medication had high success and survival rates, showing periodontal healing and resolution of signs and symptoms. However, concerning the continued root development, the outcomes can still be considered unpredictable.